Advancing Legal Citation Text Classification A Conv1D-Based Approach for Multi-Class Classification - Xie, Ying; Li, Zhengning; Yin, Yibo; Wei, Zibu; Xu, Guokun; Luo, Yang (Journal of Theory and Practice of Engineering Science, 2024)
The escalating volume and intricacy of legal documents necessitate advanced techniques for automated text classification in the legal domain. Our proposed approach leverages Convolutional Neural Networks (Conv1D), a neural network architecture adept at capturing hierarchical features in sequential data. The incorporation of max-pooling facilitates the extraction of salient features, while softmax activation enables the model to handle the multi-class nature of legal citation categorization. By addressing the limitations identified in previous studies, our model aims to advance the state-of-the-art in legal citation text classification, offering a robust and efficient solution for automated categorization in the legal domain. Our research contributes to the ongoing evolution of NLP applications in the legal field, promising enhanced accuracy and adaptability in the automated analysis of legal texts.